Repairing Behavior of Termites Odontotermes Obesus (Rambur),(Blattodea: Termitidae) in Response to the Damage of Indoor Mudtube (Global Journals of Research in Engineering, 2022)
The termite Odototermes obesus (Rambur) either tunnel through soil or move inside the #x2018;mudtube#x2019; usually found on walls or in cracks between boards and walls. The mudtube formation could provide the initial proof of the termite infestation. The study analyses the behavioral changes of termite when the indoor mudtube was damaged. The response of termites was recorded by video camera at certain intervals until the mud tube was repaired and closed. Seasonal effects on repairing of damaged mud tube by termite indicated that during rainy season the time required for repairing an unit area of indoor mud tube was about half of the summer season. Based on change of behavioral patterns due to the damage of mud tube the responses of the termites were divided into 6 different categories which reflected the different division of labors that were distributed among the workers after sudden disturbance. The studies on measuring activity of work found out the time required for different steps of work for repairing the damage.
Keywords: termite; house; mud tube; tunnel; seasons; sand